The Excitatory Synaptic Transmission of the Nucleus of Solitary Tract Was Potentiated by Chronic Myocardial Infarction in Rats - Li, Jing; Zhang, Ming-Ming; Tu, Ke; Wang, Jian; Feng, Ban; Zhang, Zi-Nan; Lei, Jie; Li, Yun-Qing; Du, Jian-Qing; Chen, Tao (PLOS ONE, 2015)
Angina pectoris is a common clinical symptom that often results from myocardial infarction. One typical characteristic of angina pectoris is that the pain does not match the severity of the myocardial ischemia. One possible explanation is that the intensity of cardiac nociceptive information could be dynamically regulated by certain brain areas. As an important nucleus for processing cardiac nociception, the nucleus of the solitary tract (NTS) has been studied to some extent. However, until now, the morphological and functional involvement of the NTS in chronic myocardial infarction (CMI) has remained unknown. In the present study, by exploring left anterior descending coronary artery ligation surgery, we found that the number of synaptophysin-immunoreactive puncta and Fos-immunoreactive neurons in the rat NTS two weeks after ligation surgery increased significantly. Excitatory pre- and postsynaptic transmission was potentiated. A bath application of a Ca2+ channel inhibitor GABApentin and Ca2+ permeable AMPA receptor antagonist NASPM could reverse the potentiated pre- and postsynaptic transmission, respectively. Meanwhile, rats with CMI showed significantly increased visceral pain behaviors. Microinjection of GABApentin or NASPM into the NTS decreased the CMI-induced visceral pain behaviors. In sum, our results suggest that the NTS is an important area for the process of cardiac afference in chronic myocardial infarction condition.